Damage to medical complexes in the Gaza Strip during the Israel-Hamas war: a geospatial analysis - Poole, Danielle N.; Andersen, Daniel; Raymond, Nathaniel A.; Grace, Rob; Smith, Trevor; Khoshnood, Kaveh; Mowafi, Hani (BMJ global health, 2024)
Introduction Medical facilities are civilian objects specially protected during armed conflict by international humanitarian law (IHL). These protections are customarily applied regardless of the conflict, parties or contexts involved. Attacks on medical care have characterised the bombardment campaign of the Gaza Strip beginning 7 October 2023. This study presents evidence regarding patterns of damage to medical complexes relative to all other buildings in the first month of this conflict. - Methods This is an observational pre/post-study of damage to buildings during the first month of the Israel Defence Force bombardment of Gaza from 7 October to 7 November 2023. Open-source polygons for the Gaza Strip were spatially joined with building damage assessments from satellite imagery analysis. Medical facilities were included in the analysis if they were cross-referenced by a minimum of two datasets. Logistic regression was used to test for statistically significant differences in the proportions of damaged medical complexes and other buildings. - Results A total of 167 292 unique buildings were identified, including 106 cross-referenced medical complexes. Approximately 9% of non-medical buildings and medical complexes alike sustained damage during the first month of the bombardment. No difference in the odds of damage was detected between medical complexes and all other buildings (OR: 0.89; 95% CI: 0.45-1.76; p>0.74). - Conclusion There is a lack of evidence of differential damage to medical and non-medical complexes during the first month of the bombing campaign. This finding raises concerns about combatants’ application of the principles of distinction, proportionality and precaution, suggesting the importance of further investigation.
Gesehen am 09.09.2024